2021
DOI: 10.3390/ijms222111529
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of Sulphation, Salt Type, and Salt Concentration on the Structural Heterogeneity of Glycosaminoglycans

Abstract: The increasing recognition of the biochemical importance of glycosaminoglycans (GAGs) has in recent times made them the center of attention of recent research investigations. It became evident that subtle conformational factors play an important role in determining the relationship between the chemical composition of GAGs and their activity. Therefore, a thorough understanding of their structural flexibility is needed, which is addressed in this work by means of all-atom molecular dynamics (MD) simulations. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 78 publications
3
16
0
Order By: Relevance
“…The Ramachandran plots showed characteristic preferences for both the 1→4- and 1→3-linked glycosidic bonds, which matched the available crystallographic data of free and protein-bound oligosaccharides ( Table S1 ). These results also correlated well with the published data using MD and NMR [ 27 , 31 , 32 , 33 , 36 , 37 ]. However, the collective analysis of all possible sequences revealed clear topological differences between the 1→4- and 1→3-linked sequences, each of which exhibited variations arising from the level of sulfation in two saccharide rings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The Ramachandran plots showed characteristic preferences for both the 1→4- and 1→3-linked glycosidic bonds, which matched the available crystallographic data of free and protein-bound oligosaccharides ( Table S1 ). These results also correlated well with the published data using MD and NMR [ 27 , 31 , 32 , 33 , 36 , 37 ]. However, the collective analysis of all possible sequences revealed clear topological differences between the 1→4- and 1→3-linked sequences, each of which exhibited variations arising from the level of sulfation in two saccharide rings.…”
Section: Discussionsupporting
confidence: 91%
“…Understanding their structural and energetic preferences may offer better insight into designing oligomeric CS sequences that selectively bind proteins of interest. The literature contains several reports on the atomistic characterization of CS building blocks using X-ray crystallography [ 26 ], NMR [ 27 , 28 , 29 ], molecular modeling (MM) [ 30 ] and molecular dynamics (MD) [ 31 , 32 , 33 ]. Insights from the NMR and crystallographic studies have shown that the backbone orientations of the polymeric scaffold changes as sulfate groups are introduced at various positions.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, computational techniques, such as MD, can offer significant insights into the dynamics of GAG chains and the molecular recognition of proteins by GAGs . Recently, the effect of sulfation and cations on the conformational properties of disaccharides of CS and HS was studied through atomistic MD simulations. , Different macroscopic hydrodynamic properties of more than a hundred residues-long heparin sulfate chain were estimated using coarse-grained simulations . Also, different long sequences such as nonsulfated conformational ensembles of 10- and 20-mers of GAG chains and a 48-monosaccharide HA oligomer with varying salt concentrations and temperature were also investigated using MD simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed solvation shell analysis revealed specific interaction points that could be occupied by Na + , which induce glycosidic dihedral conformational change that cause hairpin-like turns that compact the chain [ 126 ] ( Figure 5 ). Finally, while Na + is more likely to form direct interactions with hyaluronan than is Mg 2+ , as discussed above, K + is even more likely than Na + to form direct interactions [ 127 ]. This arises from the larger ionic radius of K + compared to Na + that, combined with polymer rigidity limitations, makes direct K + bridging of carboxylate groups more likely than solvent-separated K + bridging [ 127 ].…”
Section: Atomic-resolution Molecular Dynamics Simulations Of Hyaluron...mentioning
confidence: 99%
“…Finally, while Na + is more likely to form direct interactions with hyaluronan than is Mg 2+ , as discussed above, K + is even more likely than Na + to form direct interactions [ 127 ]. This arises from the larger ionic radius of K + compared to Na + that, combined with polymer rigidity limitations, makes direct K + bridging of carboxylate groups more likely than solvent-separated K + bridging [ 127 ].…”
Section: Atomic-resolution Molecular Dynamics Simulations Of Hyaluron...mentioning
confidence: 99%